2021
DOI: 10.3390/su13095322
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment (LCA) of an Innovative Compact Hybrid Electrical-Thermal Storage System for Residential Buildings in Mediterranean Climate

Abstract: The buildings sector is one of the least sustainable activities in the world, accounting for around 40% of the total global energy demand. With the aim to reduce the environmental impact of this sector, the use of renewable energy sources coupled with energy storage systems in buildings has been investigated in recent years. Innovative solutions for cooling, heating, and domestic hot water in buildings can contribute to the buildings’ decarbonization by achieving a reduction of building electrical consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
3
4
0
Order By: Relevance
“…In general, the impact of the heat pump appears to be always higher than that of the gas boiler. It is in accordance with previous studies, such as [17,19]. In fact, the environmental impacts of the heat pump ranged from 180 kgCO2-eq/m 2 (GWP 20a) to 81 kgCO2eq/m 2 (GWP 100a), far higher than those of the gas boiler that reached 30 kgCO2-eq/m 2 for In general, the impact of the heat pump appears to be always higher than that of the gas boiler.…”
Section: Manufacturing and Disposal Stagesupporting
confidence: 91%
See 4 more Smart Citations
“…In general, the impact of the heat pump appears to be always higher than that of the gas boiler. It is in accordance with previous studies, such as [17,19]. In fact, the environmental impacts of the heat pump ranged from 180 kgCO2-eq/m 2 (GWP 20a) to 81 kgCO2eq/m 2 (GWP 100a), far higher than those of the gas boiler that reached 30 kgCO2-eq/m 2 for In general, the impact of the heat pump appears to be always higher than that of the gas boiler.…”
Section: Manufacturing and Disposal Stagesupporting
confidence: 91%
“…The results of the analysis, performed through the ReCiPe and the IPCC global warming potential GWP indicators, showed that the total impact of the innovative hybrid energy storage system was lower than the reference one. Zsembinszki et al [19] compared the environmental performance of an innovative compact hybrid electrical-thermal storage system and a traditional system for cooling, heating, and domestic hot water production in the Mediterranean context. The authors obtained a relevant reduction in energy consumption during the operational stage with the innovative system, despite the environmental impact during its entire life cycle (30-years lifespan) being almost double than that of the traditional system.…”
Section: Life Cycle Assessment Applied To Buildingsmentioning
confidence: 99%
See 3 more Smart Citations